2018
DOI: 10.1016/j.jchf.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Supervised Exercise Training to a Post-Hospital Disease Management Program for Patients Recently Hospitalized With Acute Heart Failure

Abstract: Supervised center-based ET was a safe, feasible addition to disease management programs with supported home exercise in patients recently hospitalized with acute HF, but did not reduce combined end-point of death or readmission. (A supervised exercise programme following hospitalisation for heart failure: does it add to disease management?; ACTRN12608000263392).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
1
33
1
1
Order By: Relevance
“…Our findings suggest that exercise may reduce the risk of re‐admission after hospitalisation for HF, albeit for intermediate (90‐day) rather than short term (30‐day) re‐admissions. These findings are at variance with those of a recently published randomised trial in Queensland 25 . Exercise is usually recommended for stable patients after HF, 26 but only 10% of patients in our sample received an exercise program.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Our findings suggest that exercise may reduce the risk of re‐admission after hospitalisation for HF, albeit for intermediate (90‐day) rather than short term (30‐day) re‐admissions. These findings are at variance with those of a recently published randomised trial in Queensland 25 . Exercise is usually recommended for stable patients after HF, 26 but only 10% of patients in our sample received an exercise program.…”
Section: Discussioncontrasting
confidence: 97%
“…These findings are at variance with those of a recently published randomised trial in Queensland. 25 Exercise is usually recommended for stable patients after HF, 26 but only 10% of patients in our sample received an exercise program. We suspect that these exercise programs were implemented later rather than early in the transition phase.…”
Section: Exercise Trainingmentioning
confidence: 87%
“…Patients with multi-morbidity are more likely to have hospital utilisation unrelated to their HF diagnosis, which is unlikely to be impacted by the HF-directed intervention. Indeed, in our primary analysis we reported only 20% of hospital readmissions were due to HF, 11 consistent with large registry findings 25 and reflecting our 'real world' inclusion criteria in this trial. It is also possible that intense follow-up and monitoring within the ET+DMP group may have contributed to the increased hospital readmissions in this older subgroup with more co-morbidities.…”
Section: Discussionsupporting
confidence: 84%
“…Results of the primary effectiveness analysis of the EJECTION-HF trial have been reported elsewhere. 11 The trial did not show a significant reduction in the primary outcome of 12-month all-cause death or readmission, but pre-planned subgroup analysis showed a statistical interaction with age, suggesting greater benefit in participants aged less than 70 years. 11 Given these results, we aimed to assess the relative cost-effectiveness of supervised exercise training (ET) added to a post-discharge DMP (ET +DMP vs. DMP alone) among all study participants, those aged <70 years, and 70 years, to help inform post-discharge HF management practices.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation